Venetoclax combined with azacitidine in blastic plasmacytoid dendritic cell neoplasm: a case report and comprehensive review on the current and future treatment - Wang, Xiaoning; Guo, Jiashuo; Liu, Yan; Zheng, Na; Xu, Shaohan; Wu, Lianhui; Yuan, Ruirui; Xue, Liying; Li, Jie (Frontiers in Medicine, 2024)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an extremely rare haematological malignancy with a highly aggressive behaviour and median survival of <2 years. Especially, most BPDCN patients present with extensive and non-specific skin lesions, usually leading to misdiagnosis as a skin disease and delay therapy. As for treatment, most patients with BPDCN experience relapse shortly after treatment with the traditional regimens. The alleviation of skin symptoms reflects the effects of clinical treatments. Herein, we report a case of a 71-year-old man with intermittent and gradually expanding skin lesions over his chest, abdomen, and back for 1 year. On admission, physical examination revealed extensive skin lesions and multiple enlarged lymph nodes. Laboratory examinations showed pancytopenia and numerous malignant cells in the peripheral blood smear (60%), bone marrow aspirate smear (73.5%). Immunophenotyping using flow cytometry and immunohistochemistry presented large numbers of BPDCN cells in the bone marrow, cervical lymph nodes and dermal tissue. PET/CT revealed multiple enlarged lymph nodes and splenomegaly. Once the diagnosis was identified as BPDCN, the patient began treatment with the oral BCL2 inhibitor venetoclax and subcutaneously administered azacitidine. After the first course, skin lesions reduced markedly and complete remission was achieved in the bone marrow. Our study and current cumulative data according to reviewing systematically suggest that venetoclax combined with azacitidine is safe, effective, and applicable in the treatment of BPDCN, especially for elderly relapsed/refractory patients. This study, therefore, significantly contributes to the literature on the current and future treatment for BPDCN.